2020
DOI: 10.1176/appi.neuropsych.20010003
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Disorder Among Patients Diagnosed With Frontotemporal Dementia

Abstract: Objective: Previous studies have documented manic and hypomanic symptoms in behavioral variant frontotemporal dementia (bvFTD), suggesting a relationship between bipolar disorder and bvFTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 78 publications
0
33
0
1
Order By: Relevance
“…For instance, some individuals with late-onset BD that seemed to have bvFTD actually developed a nonprogressive dementia that mimics bvFTD. 23 The same situation was described in four patients with BD that developed a bvFTD-like syndrome without clinical or neuroimaging progression, 57 in a patient whose abnormalities in the frontal lobe improved after treatment with lithium, 58 and in a patient with BD that presented with a relapsingremitting course of bvFTD. 59 This subgroup of individuals have been referred to as nonprogressive or phenocopy cases and they present a more benign course of bvFTD, with more autonomy in daily life, lower neuropsychological impairments and none or mild changes in neuroimaging.…”
Section: Clinical Factorsmentioning
confidence: 62%
“…For instance, some individuals with late-onset BD that seemed to have bvFTD actually developed a nonprogressive dementia that mimics bvFTD. 23 The same situation was described in four patients with BD that developed a bvFTD-like syndrome without clinical or neuroimaging progression, 57 in a patient whose abnormalities in the frontal lobe improved after treatment with lithium, 58 and in a patient with BD that presented with a relapsingremitting course of bvFTD. 59 This subgroup of individuals have been referred to as nonprogressive or phenocopy cases and they present a more benign course of bvFTD, with more autonomy in daily life, lower neuropsychological impairments and none or mild changes in neuroimaging.…”
Section: Clinical Factorsmentioning
confidence: 62%
“…It has been suggested that "although the lifelong BD may go onto develop bvFTD, it is late-onset BD that carries the most significant risk for developing bvFTD" (30); however, the present study has been focused precisely on those patients with "lifelong BD, " thus including only patients classified as EO-OABD. Our approach allows us to characterize BD patients after a long progression of the disease and is motivated by the fact that EO-OABD patients constitute a population that will continue to increase.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
“…On the opposite direction, associations between bvFTD and previous psychiatric diagnosis are equally complex. The retrospective study of Mendez et al (30) revealed that 10.2% of bvFTD patients had a previous diagnosis of BD; a deeper analysis of their histories confirmed a BD diagnosis in 11 patients (8%), among whom 3 patients (2.1%) had non-progressive bvFTD while the remaining 8 patients (5.8%) fulfilled the criteria for progressive bvFTD, concluding that the relationship between bvFTD and BD may be rather heterogeneous (30). We did not identify a previous history of BD in our bvFTD sample.…”
Section: Implications Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another issue that warrants consideration when interpreting the neurocognitive heterogeneity observed among bipolar individuals is the fact that some cases of late-onset BD (LOBD) may be behavioral manifestations of other conditions that mimic the disorder. LOBD, which is associated with more severe cognitive deficits (SamamĂ©, Martino, & Strejilevich, 2013;Schouws et al, 2009) and a possible progressive course, has been proposed to be different from the 'primary' and most prevalent forms of the disorder as its etiology may be related to vascular illness or early manifestations of neurodegenerative diseases (Mendez, Parand, & Akhlaghipour, 2020;Subramaniam, Dennis, & Byrne, 2007). As evident, both illness-related processes and other clinical factors (e.g.…”
Section: Discussionmentioning
confidence: 99%